Digital Ulcer as a Rare Complication of Systemic Lupus Erythematosus: A Case Report - Adem KÜÇÜK; Sinan BAĞCACI; Yalçın SOLAK; Recep TUNÇ1 (Archives of Rheumatology, 2014)
The two most common rheumatological diseases which accompany Raynaud’s phenomenon are systemic sclerosis and systemic lupus erythematosus (SLE). Digital gangrene formation has no definitive etiology and pathogenesis, and Raynaud’s phenomenon often accompanies the necrotic lesions associated with this skin condition. Macrovascular involvement is commonly found in systemic sclerosis, but is very rare in patients with SLE. In our case, we identified ulnar artery involvement in the absence of any other risk factors associated with digital gangrene formation. Raynaud’s phenomenon is fairly common in SLE, but digital ulcers are seldomly seen. The most common cause of digital gangrene in SLE is antiphospholipid antibody syndrome (AAS). The risk factors for digital ulcers include duration of lupus, male gender, atherosclerosis, vasculitis, and AAS. Herein, we present a case with long-standing SLE who also had digital ulcers.